Pesan Dakwah di Media Sosial Instagram: Analisis Isi pada Akun @hawaariyyun - Risqal Rulloh; Muhammad N. Abdurrazaq; Sobirin Sobirin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research discusses Da'wah Messages on Instagram Social Media (Content Analysis on the @hawaariyyun account). The problem in this research discusses the analysis of da'wah messages contained in 3 Reels videos of the Instagram account @hawaariyyun for the period 05 and 08 June 2023, including the title Connection with the Prophet, Hanging out with Believers and the Quraish infidels are Genius. This research aims to determine Da'wah messages on Instagram social media (content analysis on the @hawaariyyun account). This type of research uses the type of literature study research. The method used in this research is a descriptive approach, with data collection techniques collecting and analyzing the contents of video reels by means of observation and documentation. The research results show that Da'wah messages on Instagram social media (content analysis on the @hawaariyyun account) have very positive value for its 1.1 million followers. Moreover, the Instagram Reels video uploaded by @hawaariyyun was very easy for the resource person to understand and understand. This research concludes that there are 2 categories of da'wah messages, namely aqidah and sharia. In the Aqidah category there is the creed of faith in the Messenger, while in the sharia category there is the sharia of sunnah worship and human relations .